2011
DOI: 10.1105/tpc.111.089656
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis RTNLB1 and RTNLB2 Reticulon-Like Proteins Regulate Intracellular Trafficking and Activity of the FLS2 Immune Receptor  

Abstract: Receptors localized at the plasma membrane are critical for the recognition of pathogens. The molecular determinants that regulate receptor transport to the plasma membrane are poorly understood. In a screen for proteins that interact with the FLAGELIN-SENSITIVE2 (FLS2) receptor using Arabidopsis thaliana protein microarrays, we identified the reticulon-like protein RTNLB1. We showed that FLS2 interacts in vivo with both RTNLB1 and its homolog RTNLB2 and that a Ser-rich region in the N-terminal tail of RTNLB1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 105 publications
5
61
0
Order By: Relevance
“…As FLS2 is predominantly localized in the PM before activation 34 , while the majority of CRT1 is in endomembranes 13 , an interesting question is where these immune proteins interact. Analyses of endoglycosidase H sensitivity 35 have suggested that FLS2, whether expressed in N. benthamiana or Arabidopsis, is present in both the endoplasmic reticulum and PM 36,37 . Moreover, a portion of FLS2 was found in endomembranes 36 , suggesting the CRT1-FLS2 interaction may occur in this compartment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As FLS2 is predominantly localized in the PM before activation 34 , while the majority of CRT1 is in endomembranes 13 , an interesting question is where these immune proteins interact. Analyses of endoglycosidase H sensitivity 35 have suggested that FLS2, whether expressed in N. benthamiana or Arabidopsis, is present in both the endoplasmic reticulum and PM 36,37 . Moreover, a portion of FLS2 was found in endomembranes 36 , suggesting the CRT1-FLS2 interaction may occur in this compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of endoglycosidase H sensitivity 35 have suggested that FLS2, whether expressed in N. benthamiana or Arabidopsis, is present in both the endoplasmic reticulum and PM 36,37 . Moreover, a portion of FLS2 was found in endomembranes 36 , suggesting the CRT1-FLS2 interaction may occur in this compartment. Supporting this possibility, the animal PRRs TLR9 and TLR4, key factors in modulating innate and adaptive immunity, require localization to endosomes for their functions 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that RTN family molecules could function in protein transport from the ER to other membrane compartments, including the plasma membrane, Golgi, and endosomes (40)(41)(42). For example, RTN2B enhances trafficking of glutamate transporter EAAC1 from the ER to the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Nogo-A regulates redistribution of the ER-resident chaperone protein disulfide isomerase and contributes the proper function of protein disulfide isomerase (39). Studies have shown that some RTN family molecules could also function in protein transport from ER to other membrane compartments, including the plasma membrane, Golgi, and endosomes (40)(41)(42). For example, RTN2B enhances trafficking of glutamate transporter EAAC1 from the ER to the cell surface.…”
Section: Gramd4 Binds To Nogo-b and Inhibits Nucleic Acid-induced Tlrmentioning
confidence: 99%
“…Consequently, the sensitivity or resistance of N-glycans to Endo H digestion is commonly used as a convenient assay for determining if secreted glycoproteins contain complex N-glycans (i.e., show resistance to Endo H digestion), an indication that they have exited the ER and entered the Golgi apparatus on their way to the cell surface. In plants, sensitivity to Endo H digestion has been used to assess the subcellular localization of the BRASSINOSTEROID INSENSITIVE1 (Jin et al, 2007(Jin et al, , 2009Hong et al, 2008), FLAGELLIN SENSITIVE2 (FLS2) (Lee et al, 2011), and EFR (Nekrasov et al, 2009) receptors and specifically to assay for receptor exit from the ER.…”
Section: N-glycosylation Of Srkb Is Required For the Ability Of The Smentioning
confidence: 99%